PERTANGGUNG JAWABAN HUKUM PENYIDIK KEPOLISIAN REPUBLIK INDONESIAAKIBAT TERJADINYA SALAH TANGKAP DI SISTEMPERADILAN PIDANA INDONESIA - Hasan, Muhammad Yusuf Innamul; R, Mukhlis; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
One of the problems that occur in the Criminal Justice System is the violation of rights at one or all levels of examination or investigation. An investigation is a series of actions by an investigator in terms of and according to the method regulated in this Law to seek and collect evidence which with that evidence makes clear about the crime that occurred and to find the suspect (Pasal 1 Butir 2 KUHAP). This research is a kind of normative research. Normative research is also called library research, this research is conducted aimed only at written legislation or other legal materials. This research was conducted on legal principles starting from certain areas of the legal system, by first identifying the legal rules that have been formulated in certain legislation. The results of the study show how the responsibility of the National Police Investigator in the event of a wrongful arrest while carrying out their duties and legal remedies that the suspect can take in the event of a wrongful arrest by the Police Investigator. First, the forms of accountability of Polri investigators to victims of wrongful arrests are a) immaterial responsibilities, namely, Polri investigators directly apologize to victims of wrongful arrests, both verbally and in writing; b) material responsibility, namely providing re-guidance to investigators who violate the code of ethics, furthermore, legal remedies that can be taken if there is a wrongful arrest, namely according to Pasal 1 Ayat 22 KUHAP, compensation. The legal basis for the claim for compensation is Pasal 77 Poin b KUHAP, then rehabilitation in accordance with Pasal 1 Ayat10 KUHAP in poin c. From this research, it can be concluded that the form of responsibility carried out by Polri investigators is divided into 2, namely material responsibility, namely regarding sanctions for apology statements and immaterial responsibility, namely regarding sanctions in the form of retraining obligations in Polri educational institutions. Meanwhile, legal remedies that can be taken by victims of wrongful arrests are by making demands for compensation and rehabilitation. Keywords: Responsibilities of Investigators - Legal Efforts - Victims of Wrong Arrest